Heinrich Triepel - Parteienstaat und Staatsgerichtshof Gesammelte verfassungspolitische Schriften zur Weimarer Republik - von Bogdandy, Armin (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2021)
Heinrich Triepel (1868-1946), full professor in Berlin and founder of the German constitutional law teachers' association, republican by reason and Wilhelmine-influenced monarchist of his heart, commented on the constitutional history of the Weimar years beginning in 1918 and coming to an end in 1933. He focused on fundamental developments that are still being discussed today: basic questions of constitutional policy, problems of the federal state and growing tendencies towards emergency legislation, the party state and constitutional jurisdiction. Unlike the works of other authors of the "Richtungsstreit", Triepel's Weimar writings have not been republished in postwar Germany. This collection assembles the most important texts, adding some references and annotations. An introduction puts them into a wider context. It raises the question of Triepel's constitutional position and influence, but it also considers Triepel's historically informed texts as lessons of a constitutional argumentation of lasting interest.With contributions byReinhard Mehring (Introduction) and Heinrich